Single nucleotide polymorphism (SNP) analysis of ovine progesterone receptor gene in Malpura ewes - KUMAR, RAJIV; SANKHYAN, S K; SINGH, A K; KRISHNAPPA, B (The Indian Journal of Animal Sciences, 2017)
In the present work, nucleotide sequences of progesterone receptor gene (627 bp fragments) encompassing partial ligand binding domain from repeat breeder Malpura ewes were analyzed for presence of SNPs and its association with repeat breeding. A total of 40 sequences were aligned and 13 SNPs were noted mostly in intronic region. Two novel missense mutations were observed in the ligand binding domain where histidine (H) was replaced with tyrosine (Y). These SNPs were not associated with repeat breeding in Malpura ewes.